PANDANGAN TARJIH MUHAMMADIYAH TENTANG HUKUM MA’PAPELLAO TOMATE DI DESA MUNDAN KECAMATAN MASALLE KABUPATEN ENREKANG - Ahmad Muntazar; Syafruddin; Zainal Abidin (Universitas Islam Negeri Alauddin Makassar, 2023)
Ma'papellao Tomate has been a tradition passed down from generation to generation in Masalle District, Enrekang Regency. This tradition has caused controversy among the people of Masalle District. In connection with this tradition, the community is divided into two groups: groups that allow it and groups that do not. Therefore, the author aims to find out the process of carrying out the Ma'papellao Tomate tradition and the Ma'papellao Tomate law according to the view of Muhammadiyah Tarjih. The research method used in this research is descriptive qualitative research using the 'urf. The data sources used in this research were interviews with community leaders and Muhammadiyah Tarjih. Data collection methods include interviews and observation. The results of this study show that the process of carrying out the Ma'papellao Tomate tradition is carried out on the first night, third night, and seventh night, and the peak of the event is on the forty-first day. According to the Muhammadiyah tarjih view, the Ma'pappelao Tomate tradition is a custom or tradition that is not in line with the principles of Islamic teachings, especially in matters of faith. This is due to the existence of rituals or readings that fall into the category ofbidah, which can lead the perpetrator to fall into shirk. As for the suggestion from the author that the people in the Ma'papellao Tomate tradition should not be coerced or obliged to carry it out, I do not think that disaster will occur if they do not carry out this tradition.